Proglucagon peptide secretion profiles in type 2 diabetes before and after bariatric surgery: 1-year prospective study. Issue 1 (24th March 2020) - Alexiadou, Kleopatra; Cuenco, Joyceline; Howard, James; Wewer Albrechtsen, Nicolai Jacob; Ilesanmi, Ibiyemi; Kamocka, Anna; Tharakan, George; Behary, Preeshila; Bech, Paul R; Ahmed, Ahmed R; Purkayastha, Sanjay; Wheller, Robert; et al.
Abstract : Introduction: Hyperglucagonemia is a key pathophysiological driver of type 2 diabetes. Although Roux-en-Y gastric bypass (RYGB) is a highly effective treatment for diabetes, it is presently unclear how surgery alters glucagon physiology. The aim of this study was to characterize the behavior of proglucagon-derived peptide (glucagon, glucagon-like peptide-1 (GLP-1), oxyntomodulin, glicentin) secretion after RYGB surgery. Research design and methods: Prospective study of 19 patients with obesity and pre-diabetes/diabetes undergoing RYGB. We assessed the glucose, insulin, GLP-1, glucose-dependent insulinotropic peptide (GIP), oxyntomodulin, glicentin and glucagon responses to a mixed-meal test (MMT) before and 1, 3 and 12 months after surgery. Glucagon was measured using a Mercodia glucagon ELISA using the 'Alternative' improved specificity protocol, which was validated against a reference liquid chromatography combined with mass spectrometry method. Results: After RYGB, there were early improvements in fasting glucose and glucose tolerance and the insulin response to MMT was accelerated and amplified, in parallel to significant increases in postprandial GLP-1, oxyntomodulin and glicentin secretion. There was a significant decrease in fasting glucagon levels at the later time points of 3 and 12 months after surgery. Glucagon was secreted in response to the MMT preoperatively and postoperatively in all patients and there was no significant change in this postprandial secretion. There was no significant change in GIP secretion. Conclusions: There is a clear difference in the dynamics of secretion of proglucagon peptides after RYGB. The reduction in fasting glucagon secretion may be one of the mechanisms driving later improvements in glycemia after RYGB. Trial registration number: NCT01945840 .